Evasão escolar na educação profissional: diagnóstico dos cursos técnicos subsequentes do Colégio Estadual de Pato Branco - Gugelmin, Lisangela (2015)
The Professional Education is an area of teaching deeply interrelated to the insertion of the individuals in the world of work once under the premise of their relationship between education and work. This study aimed to depict the school evasion in the subsequent courses of Colégio Estadual de Pato Branco ( CEPB) through the realization of a diagnosis about the flow of the enrolments in the courses and the measure of the identified indices of evasion in the period between 2007 to 2012, as well as to identify what are the factors that are causing that. For that, the research was divided in two different stages, the first as a quantitative one which comprehended to analyze the school institution reports in order to collect data and measure the enrolments flow and the calculation of the evasion indices, and the second one as a qualitative research through semi structures interviews in order to identify the possible factors that contribute to the school dropouts. It was identified that the CEPB technical subsequent courses registered high level of evasion during the period of 2007 and 2012, considering that the highest levels were on the Administration and Informatics Technic courses and, the first years of courses have the highest levels of evasions. It was also identified that the dropouts in the subsequent courses show complexity and results of a correlation of several elements being the social and economics the most relevant for the decision of abandoning the professional education course.